1998
DOI: 10.1111/j.1744-7348.1998.tb05221.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Pymetrozine, a feeding inhibitor of Homoptera, in preventing transmission of cauliflower mosaic caulimovirus by the aphid species Myzus persicae (Sulzer)

Abstract: Summary Mature turnip plants, mechanically infected as seedlings with the semi‐persistent, aphid transmitted caulimovirus, cauliflower mosaic (CaMV), were treated by spraying with either a solution of Pymetrozine plus adjuvant oil, adjuvant oil or water only. At the same time turnip seedlings were sprayed for each of the three treatments. Two h after spraying, Myzus persicae were caged onto an infected turnip plant for each of the three treatments. Twenty four h later, groups of 20 aphids were transferred from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In some cases, pymetrozine has been demonstrated to reduce PRLV transmission during both acquisition and inoculation (Mowry 2005). This insecticide significantly reduced the acquisition of CaMV, a semi‐persistently transmitted virus, from turnip plants by M. persicae ; whereas no viral transmission inhibition was recorded when the aphids were already viruliferous (Bedford et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some cases, pymetrozine has been demonstrated to reduce PRLV transmission during both acquisition and inoculation (Mowry 2005). This insecticide significantly reduced the acquisition of CaMV, a semi‐persistently transmitted virus, from turnip plants by M. persicae ; whereas no viral transmission inhibition was recorded when the aphids were already viruliferous (Bedford et al. 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our study pymetrozine provided adequate protection even after 7 days following the application. Previous studies with CaMV (Bedford et al. 1998) and the whitefly transmitted viruses tomato yellow leaf curl virus (TYLCV) (Polston and Sherwood 2003) a single application of pymetrozine inhibited virus transmission for 7 days, but the effectiveness was significantly reduced after 11 days post‐treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inoculation of non‐persistent viruses is associated with salivation during brief cell punctures by the stylets while that of persistent viruses is thought to occur during phloem salivation . Previous studies have often shown the application of insecticides to be beneficial in reducing the spread of plant viruses . From this study it appears that M. persicae disperses at the same rate regardless of the presence or absence of neonicotinoid treatment, hence in theory, the application of neonicotinoids should exert either a beneficial (due to increased vector mortality) or else no effect on the rates at which plant viruses spread within a crop, supporting such findings.…”
Section: Discussionmentioning
confidence: 63%
“…Aphids remain alive for 2 to 4 days before they die of starvation. Pymetrozine has been shown to reduce both direct damage and virus transmission by aphids (Bedford et al 1998). Because of its specificity for sucking insects, it is relatively nontoxic to most natural enemies (Sechser et al 2002).…”
Section: Controlling Dipteran Leafminersmentioning
confidence: 99%